STUDI TENTANG MOTIF BATIK MELAYU RIAU DI PEKANBARU - AMBAR SARI, Dra. Minarsih, M.Sn, Drs. Erwin, M.Sn (Serupa The Journal of Art Education, 2014)
As time goes by batik in Riau Province has developed very well, it showed many enthusiasts Riau Malay batik. For example, during an official ceremony in Riau Province officials and many young people wear batik patterned Malay. Batik is widely traded in stores and shopping malls in Pekanbaru. On the other hand a lot of people who do not know the meaning of Riau Malay batik itself. Community only in terms of assessing whether or not the motif used without knowing the philosophy contained therein.This study aims to: 1) Describe the various Malay batik, and 2) describe the various Malay motif of shape, color, placement, composition, and source of ideas Malay batik creation.This research is used to get an idea about the motives and meaning of Malay batik. Based on the purpose of the study, the researchers used a method kualitatif.Selain the research methodology used is a cultural approach (Etnoscience / Cognitive Anthropology) in the social and cultural life by examining the motives and meaning of Malay batik.The results showed that the wear batik motifs by local Riau (Riau motif). Batik motifs themed Riau most herbs like bulk of Mangosteen, Forest Flower, Fan Linga, Give It Up, Bud biting and so forth. Each batik Malay have their respective meanings contained in the motif.Research conclusion that each motif has Riau Malay meaning each basic motifs have meaning grandeur chrysolite floral motifs further interest basis berembang have meaning on the weak need protection while on the basis of floral motifs bridal tears have meaning hospitality to guests.